2020
DOI: 10.4012/dmj.2019-203
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibacterial calcium phosphate nanocomposite with long-term ion recharge and re-release to inhibit caries

Abstract: Short-term studies on calcium-phosphate (CaP) ion-rechargeable composites were reported. The long-term rechargeability is important but unknown. The objectives of this study were to investigate nanocomposite with strong antibacterial and ion-recharge capabilities containing dimethylaminododecyl methacrylate (DMAHDM) and nanoparticles of amorphous calcium phosphate (NACP), and evaluate long-term ion-recharge by testing for 12 cycles (taking 6 months to complete) for the first time. Three groups were tested: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…All studies reported that composites with DMAHDM had significantly reduced live bacteria than control composites. Among the ten studies that assessed the antibacterial potential of NACP alone, all reported similar results to control composites where bacteria were primarily alive, indicating NACP did not have any additional antibacterial effects with DMAHDM [ 1 , 2 , 37 , 42 , 46 ]. Composites with MPC alone showed lower levels of bacterial adhesion but the bacteria were found to be mostly alive; however, when combined with DMAHDM, there were less biofilms and the bacteria had mostly compromised cell membranes [ 3 , 38 , 40 , 43 , 44 , 45 ] with no significant changes in results after 180 days of water-aging [ 45 ].…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…All studies reported that composites with DMAHDM had significantly reduced live bacteria than control composites. Among the ten studies that assessed the antibacterial potential of NACP alone, all reported similar results to control composites where bacteria were primarily alive, indicating NACP did not have any additional antibacterial effects with DMAHDM [ 1 , 2 , 37 , 42 , 46 ]. Composites with MPC alone showed lower levels of bacterial adhesion but the bacteria were found to be mostly alive; however, when combined with DMAHDM, there were less biofilms and the bacteria had mostly compromised cell membranes [ 3 , 38 , 40 , 43 , 44 , 45 ] with no significant changes in results after 180 days of water-aging [ 45 ].…”
Section: Resultsmentioning
confidence: 97%
“…All studies used a modified Menschutkin reaction method to synthesize DMAHDM [ 2 ]. NACP was synthesized with a spray-drying technique [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations